Report of a wild population of Sedum morganianum E. Walther (Crassulaceae) - Jimeno-Sevilla, H. David; Cházaro-Basáñez, Miguel; Albalat-Botana, Amparo (Instituto de Ecología, A.C., 2010)
Over 70 years after its original description, Sedum morganianum E. Wather, the “donkey tail”, has been at last found wild in two ravines at Tenampa county, in central Veracruz, in eastern Mexico. It grows on vertical cliffs of igneous rock in the Tropical Deciduous Forest zone. For its restricted geographic distribution it should be regarded as a micro endemic species.